Progressivitas Perilaku Hidup Bersih dan Sehat Menuju Adaptasi Kebiasaan Baru (AKB) di Kota Binjai - Rapotan Hasibuan; Nursakinah Hayati (Pro Health Jurnal Ilmiah Kesehatan, 2021)
Corona Virus Disease (COVID-19) is an infectious disease caused by a type of coronavirus that was only discovered in 2020. This virus and the disease were previously unknown before it broke out in Wuhan, China, in December 2019. WHO declared the Covid-19 pandemic on March 11, 2020, in which one of the countries affected was Indonesia. The number of positive cases of Covid-19 in North Sumatra until August 2020 was 5,898 people, of whom 2,833 people recovered and 260 died. In Binjai City, there were 104 positive cases of Covid-19 by the end of August 2020, of whom 28Â  people recovered and 10 died. This study, therefore, aims to determine the overview of efforts living healthy (PHBS) towards New Norm (AKB) in Binjai Barat District, Sukaramai Village. A qualitative approach with a case study design was used for this research. In-depth interviews, observation and documentation were conducted for data collection from 5 informants, namely the person who lives in Sukaramai Village with a total population of 9,268 people. This study found the people of West Binjai city have good behaviour towards the New Norm. These were evidenced by the information of several informants and the relatively low number of Covid-19 case. Based on the results of research in the field on community behaviour which includes knowledge, benefits, and attitudes of PHBS, it can be concluded overall that residents have appropriate attitudes and support for living healthy (PHBS).